2018
DOI: 10.1021/acs.jpcc.8b01495
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Fine Tuning of the Plasmonic Properties of Au Lattice Structures

Abstract: We tuned the plasmonic properties of the Au lattice structure by electrochemical potential control. Au lattice structures with different values of the spacing, diameter, and height show characteristic optical properties determined by the surface lattice resonance of the localized surface plasmon mode. Electrochemical potential control can change the metal structures through metal dissolution, as well as the energy of the electrons in metals. In situ real time observation of the optical properties of Au lattice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Particularly, chemical changes due to electrochemical reactions offer a unique approach for electrically controllable plasmonics that are sensitive to the chemical constituent and the surface carrier properties of the nanostructures. Electrochemical potential controlled plasmonic devices have recently been reported and should prove useful for active and fine tuning of plasmonic properties of metallic metasurfaces . Dramatic plasmonic resonance tuning based on surface‐charge density modulation was first observed in arrays consisting of 10 nm thick gold SRR and has been recently reidentified in gold nanoporous systems with remarkable surface‐to‐volume ratios .…”
Section: Other Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, chemical changes due to electrochemical reactions offer a unique approach for electrically controllable plasmonics that are sensitive to the chemical constituent and the surface carrier properties of the nanostructures. Electrochemical potential controlled plasmonic devices have recently been reported and should prove useful for active and fine tuning of plasmonic properties of metallic metasurfaces . Dramatic plasmonic resonance tuning based on surface‐charge density modulation was first observed in arrays consisting of 10 nm thick gold SRR and has been recently reidentified in gold nanoporous systems with remarkable surface‐to‐volume ratios .…”
Section: Other Materials and Methodsmentioning
confidence: 99%
“…Harnessing the Ag–AgCl redox chemical reaction, Byers et al have demonstrated a reversibly tunable resonance of silver‐based plasmonic nanoparticles . Similarly, by electrochemically controlling the structure of nanoantennas through metal dissolution, Minamimoto et al recently have reported fine tuning of the plasmonic behavior of gold nanodisk arrays . Wang et al have demonstrated real‐time color control of plasmonic metasurfaces based on the combination of bimetallic nanodot arrays and electrochemical bias .…”
Section: Other Materials and Methodsmentioning
confidence: 99%
“…Large wavelength shift of plasmonic antennas has been realized using this approach [220][221][222]. The second technique involves chemical changes of the meta-atoms instigated by electrochemical redox reactions in metals [223][224][225][226] or mobile ion intercalation in transition metal oxides [227]. Active metasurfaces with reversible and nonvolatile switching behavior have been materialized using this technique [227].…”
Section: Electrochemical Modulationmentioning
confidence: 99%
“…The behavior can be observed in nanoparticles, nanorods, nanodimers, and Au lattices. [91][92][93][94] The rate of electrodissolution can be adjusted (accelerated by laser excitations with hot holes, 95 inhibited with low concentrations of oxoanions 96 ). Under potential deposition (UPD) 97 technologies can also be applied for metal dissolution of Au dimer structures.…”
Section: Hybrid Manipulationmentioning
confidence: 99%